2020
DOI: 10.1128/mra.00862-20
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Lactococcus lactis Strains MS22314, MS22333, MS22336, and MS22337, Isolated from Fermented Camel Milk in Ethiopia

Abstract: The genome sequences of four Lactococcus lactis strains isolated from fermented camel milk were sequenced using paired-end Illumina MiSeq reads. The genome size of each strain was about 2.6 Mb, and three of the strains were annotated with tet(S) coding for tetracycline resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was recently demonstrated that proteolysis is the bottleneck for acidification of camel milk with commercially available dairy starter cultures ( Berhe et al, 2018 ). LAB strains able to acidify camel milk have been isolated ( Abdelgadir et al, 2008 ; Drici, 2008 ; Drici et al, 2010 ; Gabed et al, 2015 ; Fugl et al, 2017 ) and several of these have been genome sequenced ( Drici, 2008 ; Gabed et al, 2015 ; Bragason et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was recently demonstrated that proteolysis is the bottleneck for acidification of camel milk with commercially available dairy starter cultures ( Berhe et al, 2018 ). LAB strains able to acidify camel milk have been isolated ( Abdelgadir et al, 2008 ; Drici, 2008 ; Drici et al, 2010 ; Gabed et al, 2015 ; Fugl et al, 2017 ) and several of these have been genome sequenced ( Drici, 2008 ; Gabed et al, 2015 ; Bragason et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published the genome sequences of L. lactis MS22314, MS22333, MS22336 and MS22337 (Bragason et al, 2020), where annotation of the contigs showed that MS22333 were the only strain without any genes coding for antibiotic resistance. Starter cultures containing resistance genes can possibly be a critical source of spreading antibiotic resistance, and studies have found multiple starter cultures with resistance genes (Kastner et al, 2006;Katla, Kruse, Johnsen, & Herikstad, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the strains MS22314, MS22333, MS22336 and MS22337 were isolated from spontaneous fermented camel milk in Ethiopia (Fugl et al, 2017). Genome sequences of the strains can be accessed at the Genbank under BioSample numbers: SAMN13701540, SAMN13701541, 76 SAMN13701542, SAMN13701543 (Bragason, Svendsen, Guya, Berhe, & Hansen, 2020). The cultures were grown for 24 h at 30 °C in M17 broth (Oxoid, Thermo Scientific, Hampshire, UK) containing 0.5% lactose.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…It was recently demonstrated that proteolysis is the bottleneck for acidification of camel milk with commercially available dairy starter cultures (Berhe et al, 2018). LAB strains able to acidify camel milk have been isolated (Abdelgadir et al, 2008;Drici, 2008;Drici et al, 2010;Gabed et al, 2015;Fugl et al, 2017) and several of these have been genome sequenced (Drici, 2008;Gabed et al, 2015;Bragason et al, 2020).…”
Section: Introductionmentioning
confidence: 99%